2020
DOI: 10.1097/mlr.0000000000001418
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Social Determinants of Health ICD-10 Z-Codes Among Hospitalized Patients in the United States, 2016–2017

Abstract: Background: The inclusion of Z-codes for social determinants of health (SDOH) in the 10th revision of the International Classification of Diseases (ICD-10) may offer an opportunity to improve data collection of SDOH, but no characterization of their utilization exists on a national all-payer level. Objective: To examine the prevalence of SDOH Z-codes and compare characteristics of patients with and without Z-codes and hospitals that do and do not use Z-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
87
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(105 citation statements)
references
References 10 publications
2
87
0
Order By: Relevance
“…Nevertheless, our findings add to the growing evidence that ICD-10 Z codes are significantly underutilized as a method of documenting diagnoses [13,[17][18][19]. In this sample, nearly 15% of patients had at least one ICD-10 Z code, whereas other studies have reported the prevalence of ICD-10 Z codes at around 2% [17,39]. Even in this instance of more common usage, ICD-10 Z codes still underestimated the prevalence of social risk factors and are limited in their potential to effectively infer the presence of a social factor for a patient.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Nevertheless, our findings add to the growing evidence that ICD-10 Z codes are significantly underutilized as a method of documenting diagnoses [13,[17][18][19]. In this sample, nearly 15% of patients had at least one ICD-10 Z code, whereas other studies have reported the prevalence of ICD-10 Z codes at around 2% [17,39]. Even in this instance of more common usage, ICD-10 Z codes still underestimated the prevalence of social risk factors and are limited in their potential to effectively infer the presence of a social factor for a patient.…”
Section: Discussionsupporting
confidence: 62%
“…As identification of patients' social factors is critical to organizational operations, population health, and current health policy, current The introduction of ICD-10 Z codes for social risks factors has been an exciting development for those interested in population health and an important step towards potential reimbursement for health care organizations [38]. Nevertheless, our findings add to the growing evidence that ICD-10 Z codes are significantly underutilized as a method of documenting diagnoses [13,[17][18][19]. In this sample, nearly 15% of patients had at least one ICD-10 Z code, whereas other studies have reported the prevalence of ICD-10 Z codes at around 2% [17,39].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Beginning in 2015, with the expansion of disease codes under the 10th revision of International Classification of Diseases, providers can code for SDOH with Z-codes. Expanding codes to include SDOH is an opportunity to document the extent of specific SDOH needs within the health care system; however, they are underutilized [ 8 ]. States have also incentivized collaborations between communities and HCOs, including several that specifically help rural communities advance population health [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…One drawback of reliance on insurance claims data and EHRs is that they miss social and behavioral factors that complicate care (21). Although, there is a subset of ICD-10-CM codes, the Z codes, for documenting SDOH in EHRs, these codes are underutilized (22,23). As such, SDOH Z codes may not reflect the actual burden of social needs experienced by patients.…”
Section: Introductionmentioning
confidence: 99%